Effect of Toll‐like receptor 4 on depressive‐like behaviors induced by chronic social defeat stress. Issue 3 (16th January 2020) - Zhang, Ke; Lin, Wenjuan; Zhang, Juntao; Zhao, Yawei; Wang, Xiaqing; Zhao, Mei
Abstract: Introduction: A growing body of evidence suggests that stress is an important factor in depression, and pro‐inflammatory cytokines contribute to the occurrence and development of depression in both animal models and human patients. Toll‐like receptor 4 (TLR4) has been shown to be a key innate immune pattern recognition receptor involved in the regulation of stress responses and inflammation. However, the exact effects of TLR4 on depressive‐like behaviors induced by chronic social defeat stress (CSDS) are not known. Methods: In this study, the effects of TLR4 on depressive‐like behaviors were investigated in an animal model of depression induced by CSDS. The depressive‐like behaviors were assessed by forced swimming test (FST), social interaction test (SIT), and light–dark box test (LDT). The protein expressions of TLR4 and tumor necrosis factor‐α (TNF‐α) in the hippocampus were measured using Western blotting. Results: We found that CSDS increased TLR4 protein levels in the hippocampus and induced behavioral despair in FST, social avoidance in SIT, and anxiety‐like behavior in LDT. Fluoxetine normalized the increased expression of TLR4 and reversed behavioral despair, social avoidance, as well as anxiety‐like behavior induced by CSDS. However, directly blocking TLR4, by using either TLR4 inhibitor TAK‐242 or knockout of TLR4, only inhibited behavioral despair, but not social avoidance or anxiety‐like behavior induced by CSDS. Conclusions: These results demonstrate a specific modulating role of TLR4 in behavioral despair induced by CSDS and suggest that TAK‐242 may be a beneficial treatment for patients with behavioral despair. Abstract : These results demonstrate a specific modulating role of Toll‐like receptor 4 (TLR4) in behavioral despair induced by chronic social defeat stress.